Design, development and performance of a disc plough combined with rotary blades - Hashemi, Ali (2012)
This research focused on the development of a new combined tillage machine for adequate clod breaking/pulverizing in a single pass. A disc plough combined with rotary blades (Comboplow) for land preparation was designed, fabricated and tested at Universiti Putra Malaysia (UPM) Research Farm. The machine consists of a chassis, three point hitch, transmission system (universal joint with safety clutch, gear box, input shaft, output shaft, chain, sprockets, main shaft, and holder of blades), disc, rear wheel, rotary blades and adjusting mechanism. The Comboplow includes two units of tillage tool comprising of a disc plough and several rotary blades. The disc plough cuts partially or completely inverts a layer of soil to bury surface material. The soil in contact with the surface of disc would be cut and pulverized by the rotary blades. Multiple tillage operations are reduced to a single pass and thus reduce the number of field trips as compared to conventional tillage practices resulting in reductions of soil compaction, labour, fuel cost and operation time. The rotary blades can be adjusted to certain speed and depth with the help of changing the sprockets and nuts, respectively. The Comboplow, was tested in the Serdang sandy clay loam soil texture for energy consumption and some soil characterization parameters. The tests were performed based on 2×3 factorial treatment in RCBD experimental design with three replications. Block dimensions were 25m×27m. The treatments were three types of blade (straight, curved, and L-shaped) and three rotary speeds (130 rpm, 147 rpm and 165 rpm). The parameters measured were consumption of energy, bulk density, moisture content, Mean Weight Diameter dry basis (MWDdry), Mean Weight Diameter wet basis (MWDwet),Stability Index (SI), Instability Index (II), 2<Aggregate Size Distribution<8mm (ASDd8) and 0<Aggregate Size Distribution <100mm (MWDd100). The analysis of variance (ANOVA) and Duncan’s new multiple range test were used to analyze the data using the statistical analysis systems. The results showed that MWDdry was significantly affected by types of blades. However the highest MWDdry was obtained from L-shaped blade. The rotational speed of blade was found to have significant effect on the percentage of soil bulk density (dry basis) at the lowest percentage of 15.63% for the speed of 130 rpm. MWDdry and MWDwet were found to be significantly affected by the rotational speed of blade with the lowest values of 3.12 mm and 1.39 mm for the rotational speed 165 rpm and 130 rpm, respectively. Stability index, instability index, means weight diameter of soil aggregates<100 mm and percentage of aggregates >2 mm were found to be significantly affected by the rotational speed of blade. The lowest value of stability index was 0.52 for the rotational speed of 130 rpm. Also the lowest values of instability index, mean weight diameter of soil aggregates<100 mm and percentage of aggregates >2 mm were 1.40,20.72 mm, and 56.36% for the rotational speed of 165 rpm, respectively. The draft force for tillage by the disc plough without rotary blade was 4.24 kN. The force needed to till with Comboplow working with three straight blades, three curved blades, three L-shaped blades and nine straight blades were 3.40 kN, 3.39 kN,3.75 kN and 3.70 kN, respectively. The disc plough combined with rotary blades operated well at the field speeds of 6-7.2 km/h. In the field tests, the average values of the effective filed capacity (EFC) and field efficiency (FE) of the machine were found to be 1.09 ha/8h day and 75.06% , respectively.